LAB-SCALE PRODUCTION OF RHAMNOLIPID BY PSEUDOMONAS AERUGINOSA A3 AND STUDY ITS SYNERGISTIC EFFECT WITH CERTAIN ANTIBIOTICS AGAINST SOME PATHOGENIC BACTERIA - & et al., Faqri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to obtain the considerable amount of the biosurfactant (rhamnolipid) from local isolate of Pseudomonas aeruginosa on industrial-scale. A 7L laboratory bioreactor was appointed to accomplish this task and all conditions of production were set as previously by batch culture experiments. Bioreactor with 3.5 L working volume was conducted for 120 h to obtain 16 g/L at 30ºC and 6.5 pH. The supernatant of production medium was used to reduce the surface tension of water from 72 to 27 mN/m, and the emulsification index was reached to 67%. The product was extracted with a mixture of solvents, purified by silica gel using a column of glass chromatography (3.5 × 30cm), and characterized by TLC and FTIR where it turn out that the biosurfactant is composed of both mono- and di-rhamnolipid. Mono-RL was tested for its antibacterial activity against some clinical isolates of Gram-positive and Gram-negative bacteria to obtain the MIC, which was about 250µg/ml, also at same concentration, the toxicity against Rat embryonic fibroblast (REF) cell line was reached to 23%. The combination effect of Mono-RL with some antibiotics was studied against pathogenic clinical isolates revealed that there is a synergistic effect with ampicillin against S. aureus and Serratia marcescens, with cefotaxime against E. coli and Kelbsiella pneumoniae, same as with tetracycline.